2018
DOI: 10.2478/v10038-012-0031-4
|View full text |Cite
|
Sign up to set email alerts
|

Self-efficacy, self-esteem and body image as psychological determinants of 15-year-old adolescents’ physical activity levels

Abstract: Purpose. The aim of the study was to analyze which psychological factors can determine the physical activity levels of 15-yearold adolescents. The psychological factors examined were self-efficacy, physical self-esteem (body weight and body appearance) and body image. A multifactorial perspective based on a socioecological approach as well as bandura's social learning theory was used to clarify the relationships between the determinants and physical activity levels. Methods. The study participants were 2277 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
1
2

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 13 publications
4
25
1
2
Order By: Relevance
“…Finne, Bucksch, Lampert, and Kolip (2011) have found associations between negative body image and low level of physical activity among 6630 German girls and boys aged 11-17 years. Similar findings were observed in other studies (e.g., Fountoulakis & Grogan, 2014;Kołoło, Guszkowska, Mazur, & Dzielska, 2012).…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…Finne, Bucksch, Lampert, and Kolip (2011) have found associations between negative body image and low level of physical activity among 6630 German girls and boys aged 11-17 years. Similar findings were observed in other studies (e.g., Fountoulakis & Grogan, 2014;Kołoło, Guszkowska, Mazur, & Dzielska, 2012).…”
Section: Introductionsupporting
confidence: 86%
“…The original scale was translated into the national (Polish) language, then translated back into English for checking by the International Coordinating Centre of Health Behavior in Schoolaged Children project (Currie et al, 2008;Kołoło et al, 2012). In the present study, the scale's internal consistency established with the Cronbach's alpha test was .914.…”
Section: Body Image Measurementioning
confidence: 99%
“…As the physical activity of the students increases, their social physique anxiety decreases. When these results are compared to those of other researchers, they seem to be similar (5,17,37,38). According to the conclusion of our study, the adolescents with low social physique anxiety have enough motivation to take part in physical activities and they can be said to have overcome the internal or external barriers.…”
Section: Conclusion and Discussionsupporting
confidence: 81%
“…The Effect of Physical Activity on Social Physique Anxiety and Academic Achievement in the 8th Grade Secondary School Students the individuals who are engaged in sports and exercise tend to have less social physique anxiety than those who are not [14,15]. Again some studies point at a negative correlation between the body image and physical activity [5,16,17] and physical activity and social physique anxiety (4,18). Some researchers disagree with this view and indicate that there is no such correlation [10,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies investigating behavioural determinants for PA in youth have reported that selfefficacy was linked to PA patterns, with particular importance for adolescent girls (Motl, Dishman, Saunders, Dowda, & Pate, 2007;Nalecz, Guszkowska, Mazur, & Dzielska, 2012;Rutkowski & Connelly, 2012;Sallis, Prochaska, & Taylor, 2000). Commonly, self-efficacy is understood as a domain-specific construct (Bandura, 1997); nonetheless, many researchers have used the domain-unspecific construct of General Self-Efficacy (GSE) in their investigations with PA behaviour (Nalecz et al, 2012;Sallis et al, 2000;Sawari & Mansor, 2013), which describes a relatively stable sense of perceived competence to deal with a variety of stressful situations in an efficient way (Schwarzer, 1992) and to engage in PA (Sallis et al, 2000). In Canada, a study found that self-efficacy was an important correlate of PA among adolescent girls; boys were generally more physically active and reported higher levels of GSE for PA than girls (Spence et al, 2010).…”
Section: Psychological Factors Of Pa In Adolescent Populationsmentioning
confidence: 99%